Synthesis and functionalisation of endohedral nitrogen fullerenes: towards quantum devices - Zhou, S (2017)
Endohedral nitrogen fullerenes (ENFs) have been proposed as building blocks for quantum information processing due to very long relaxation time for their incarcerated electron spins. However, fabricating quantum devices based on this exotic material is still limited by the low yield of ENFs synthesis and various difficulties in subsequent molecular engineering, including the chemical sensitivity of the molecules, assembling approaches of the molecular architecture, and control of spin-spin coupling between qubits. My contributions towards removing the aforementioned limitations by studying the synthesis and functionalisation of ENFs are presented herein. My aim has been to pave the way towards quantum devices based on ENFs. Firstly, I enhanced the ENFs production yield by a factor of five. I accomplished this by optimizing the ion implantation apparatus and parameters during the synthesis of raw ENFs, in addition to adjusting the column and eluent during the purification of ENFs by high performance liquid chromatography (HPLC). Secondly, I established (for the first time) a spin-compatible protocol for performing Bingel reactions on ENFs. Utilizing the developed method, I also demonstrated the feasibility of chemically modifying ENFs for different molecular requirements via synthesizing a series of ENF derivatives with rigid configuration, long molecular aspect ratio, and amphiphilic properties. Subsequently, I covalently assembled ENFs at microscopic levels and axially aligned ENFs at macroscopic levels, respectively. At the microscopic scale, I synthesized ENF- containing dyads and dimers, and developed a method of coaxially dimerizing ENFs with rigid bridge molecules, which provides material foundation for multi-qubit manipulations with spin couplings. At the macroscopic scale, I achieved the best orientational alignment of ENFs reported to date by embedding elongated ENF derivatives within a liquid crystal, which is critical for ensemble qubit with anisotropic spin properties. Benefiting from the good alignment, a controllability of the ensemble spin anisotropy is demonstrated with zero-field splitting of ENF derivatives. Finally, I studied the electron spin dipolar coupling in ENFs by measuring and comparing of the coupling strength at different conditions. I discovered that the electron spin dipolar coupling in N@C60-CuPc dyads can be chemically tuned by altering the lengths of the spacing groups between the two spin centres, and be physically adjusted by changing the sample concentrations to aggregate the sample and suppress the Cu electron spin. In summary, aiming for ENF-based quantum devices, I made progress in both the material production and the molecular engineering of ENFs.